A Phase 2a Study to Evaluate the Safety of MEDI8852 in Outpatient Adults with Acute, Uncomplicated Influenza A. (4th October 2017) - Ali, Omar; Takas, Therese; Nyborg, Andrew C; Jensen, Kathryn M; Dubovsky, Filip; Mallory, Raburn
Abstract: Background: Influenza is responsible for significant morbidity and mortality and more effective therapeutics are needed. MEDI8852 is a human IgG1 kappa monoclonal antibody that binds to the conserved stalk region of the influenza hemagglutinin protein neutralizing both seasonal and pandemic influenza A strains. MEDI8852 is being developed to treat patients hospitalized with influenza A. The primary objective of this study was to evaluate the safety of MEDI8852 administered either alone or with oseltamivir (OS) in outpatient adults with acute, uncomplicated influenza A. Methods: Subjects aged 18 to 65 years with onset of influenza symptoms ≤ 5 days prior to dosing were enrolled. Subjects were randomized into 4 cohorts: Cohort 1: 750 mg MEDI8852 (single intravenous infusion) + 75 mg OS (orally twice a day for 5 days); Cohort 2: 3, 000 mg MEDI8852 + 75 mg OS; Cohort 3: placebo + 75 mg OS; or Cohort 4: 3, 000 mg MEDI8852. Subjects were followed through Day 10 for solicited symptoms (SS), through Day 28 for adverse events (AEs) and through Day 101 for serious AEs (SAEs) and AEs of special interest (AESIs). Viral shedding was assessed using quantitative reverse transcription polymerase chain reaction (qRT-PCR) through Day 7. Results: 126 subjects (31 in Cohort 1; 31 in Cohort 2; 32 in Cohort 3; and 32 in Cohort 4) were enrolled at sites in United States (2015–16) and South Africa (2016). More AEs were reported in the total MEDI8852 group (Cohorts 1, 2 and 4 combined: 39/93, 41.9%) than in placebo group (10/32, 31.3%). Related AEs were similar across the 2 groups (14/93, 15.1% total MEDI8852 group; 5/32, 15.6% placebo group). Most AEs were Grade 1 or Grade 2. The most common AE was bronchitis (11/93, 11.8%; 1/32, 3.1%). One subject in Cohort 2 had a related SAE (and AESI) of Grade 3 infusion-related reaction, which resolved with treatment. There were no deaths or discontinuations due to an AE. Median (range) time to resolution of SS were similar across groups (93/94, 111.3 [92.4, 130.8] hours; 32/32, 108.8 [71.2, 161.8] hours). Median (range) decreases in viral shedding (log10 viral copies/mL) were similar across groups (-3.6 [-6.2. 0.5]; -3.4 [-5.9, 0.9]). Conclusion: MEDI8852 has an acceptable safety profile in adults with acute, uncomplicated influenza A. These results support the continued development of MEDI8852 for the treatment of influenza A. Disclosures: O. Ali, MedImmune: Employee, Salary; T. Takas, MedImmune: Employee and Shareholder, Salary and stock; A. C. Nyborg, MedImmune: Employee, Salary; K. M. Jensen, MedImmune: Employee and Shareholder, Salary and stock; F. Dubovsky, MedImmune: Employee and Shareholder, Salary and stock; R. Mallory, MedImmune: Employee, Salary